2014
DOI: 10.1007/s10661-014-3908-1
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative influences of a small city and former mining activities on the sediment quality of a subtropical estuarine protected area

Abstract: This study aimed to evaluate the sediment quality in the estuarine protected area known as Cananéia-Iguape-Peruíbe (CIP-PA), located on the southeastern coast of Brazil. The study was designed considering possible negative effects induced by the city of Cananéia on the sediment quality of surrounding areas. This evaluation was performed using chemical and ecotoxicological analyses. Sediments were predominantly sandy, with low CaCO3 contents. Amounts of organic matter varied, but higher contents occurred closer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 31 publications
7
28
0
9
Order By: Relevance
“…Additionally, the seasons also sometimes play an important role in the bioaccumulation of metals, depending on the site studied. The current findings corroborate the study by Cruz et al (2014) in which the sediment quality of the APA-CIP was assessed using ecotoxicological tools. The study concluded that the contamination from both the RIR and urban areas (the city of Cananéia) are relevant sources of pollution in the APA-CIP.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Additionally, the seasons also sometimes play an important role in the bioaccumulation of metals, depending on the site studied. The current findings corroborate the study by Cruz et al (2014) in which the sediment quality of the APA-CIP was assessed using ecotoxicological tools. The study concluded that the contamination from both the RIR and urban areas (the city of Cananéia) are relevant sources of pollution in the APA-CIP.…”
Section: Discussionsupporting
confidence: 90%
“…High levels of metals (Pb, Zn, Cu, Cr, As) recorded in river waters, bottom sediments, and suspended sediments were largely linked to mining activities in the river headwaters (Eysink et al 1988;Corsi and Landim 2003;Moraes 2004;Guimarães and Sígolo 2008). In the estuary, metals in sediments have been generally found only at moderate levels (Mahiques et al 2009;Azevedo et al 2011;Cruz et al 2014); however, these values have increased substantially since the opening of the Valo Grande channel and even more so after industrial mining activities began (Mahiques et al 2009). These reports show that metals in the APA-CIP are largely from anthropogenic sources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isso é corroborado pelo reportado por Gusso- Choueri et al (2015), que detectaram metabólitos de metais e HPAs em bile de peixes demersais (C. spixii) associada a respostas antioxidantes, estresse oxidativo, neurotoxicidade e genotoxicidade. Os autores identificaram que efluentes urbanos da cidade de Cananéia e a drenagem fluvial do Rio Ribeira de Iguape foram identificados como as principais fontes de poluição desta região (Cruz et al, 2014;Gusso-Choueri et al, 2015). O fato das respostas aparecerem majoritariamente durante a primavera-verão pode estar associada tanto à flutuabilidade da densidade demográfica em função do turismo, que acarreta em maior volume de esgotos descartados, quanto à sazonalidade, com a qual variam os índices pluviométricos da região (CETESB, 2017;Gusso-Choueri et al, 2015).…”
Section: Ostras C Brasilianaunclassified